A Review on Solid Dispersion and Carriers Used Therein for Solubility Enhancement of Poorly Water Soluble Drugs - Avinash Ramrao Tekade; Jyoti Narayan Yadav (Tabriz University of Medical Sciences, 2020)
A large number of hydrophilic and hydrophobic carriers in pharmaceutical excipients are available today which are used for formulation of solid dispersions. Depending on nature of carriers the immediate release solid dispersions and/or controlled release solid dispersions can be formulated. Initially crystalline carriers were used which are transformed into amorphous solid dispersions with enhanced properties. The carriers used previously were mostly synthetic one. Recent trend towards the use of natural carriers have replaced the use of synthetic carriers. This review is the overview of various synthetic, natural, semisynthetic, modified natural hydrophilic carriers used for formulation of solid dispersions.